THE INFLUENCE OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PERFORMANCE ON FIRM VALUE WITH THE FIRM LIFE CYCLE AS A MODERATING VARIABLE - Nunik Nurmalasari; Regina Zahra Kirana (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2024)
The primary objective of companies today is not only to maximize financial profits but also to achieve sustainability through Environmental, Social, and Governance (ESG) performance, which has become a critical factor in determining overall company value. The impact of ESG performance on firm value, however, may vary depending on the firm's life cycle stage, including the phases of establishment, growth, maturity, and decline. This study aims to examine the moderating role of the firm life cycle in the relationship between ESG performance and firm value. ESG performance is measured using the ESG score by the number of ESG disclosures, while firm value is assessed through Tobin’s Q. The firm life cycle is evaluated using two proxies: Retained Earnings to Total Assets (RE/TA) and Retained Earnings to Total Equity (RE/TE). A sample of 27 companies listed in the IDX ESG Leaders Index for the 2022-2023 period, resulting in 54 observations, was analyzed using purposive sampling. The study employs classical assumption tests, panel data regression, hypothesis testing, and moderated regression analysis (MRA) with Eviews12. The results indicate that ESG performance significantly influences firm value. Additionally, the firm life cycle, as measured by RE/TA, positively moderates the relationship between ESG performance and firm value, while RE/TE shows a negative moderating effect. These findings suggest that companies should prioritize improving their ESG performance, particularly during certain stages of the life cycle, to maximize their value.